PETITION AS INDONESIAN FILM’S ROBBER: Theodor Adorno’s Perspective on Majority-Leaning Group’s Criticisms - Nugroho, Sri Nugroho (Seni Media Rekam ISI Surakarta, 2021)
Filmmakers have felt the impact of numerous films that have been petitioned or rejected by groups acting in the majority’s interests. The groups carry religious issues and view films as a new force capable of undermining the values (dogma) they believe. The views were infiltrated by efforts to homogenize discourses for a particular purpose rather than pure objectivity, resulting in petitions opposing certain films. In this regard, Adorno’s perspective on the revolutionary objective basis leads to the eradication of critical thinking against individuals associated with capitalism. The term “capitalists” refer to persons who control the Indonesian film industry. The underlying phenomena of this research are alienation and oppression, and the research sources are film industry actors who are directly affected by the phenomena above. Using Bogdan’s and Taylor’s qualitative approach in Moleong (2018), this study reveals that capitalists attempt to paralyze the joints of critical thinking to steer Indonesian films toward uniform themes, namely religious ones, that are “safe” from mass organizations’ petitions and rejections. These efforts mark the end of critical thinking and ideas in the creative filmmaking process.